Relation between Global Solar Radiation and Solar Ultraviolet Radiation in Different Parts of Nepal - Pokhrel, Rudra P; Bhattarai, Binod K (Journal of the Institute of Engineering, 2012)
Part of the solar spectrum whose wavelength lies between 40 to 400 nm is called Solar Ultraviolet radiation. Solar UV Index (UVI) is the measure of the UV radiation level at a place, which plays the important role to raise public awareness and alert people to use protective measures when exposed to UV radiation. This study tries to find out the UV radiation level at a place by knowing the global radiation and will help to find out the UV radiation level at different places where UV radiation measuring instruments are not easily accessible. By the study of the relationship between global solar radiation and Solar Ultraviolet radiation at different sites (Biratnagar, Lukla, Kathmandu and Pokhara) of Nepal, simple regression equations were obtained. UV radiation level at a place was retrieved by using this equation. Ground based global solar radiation were measured by using radiation measuring instrument, Pyranometer (CMP6), manufactured by Kipp and Zonen, Netherland. A comparison between equation based calculation and ground based measurement of UV level (using NLU-UV meter) shows the average deviation of 3% at Lukla, 7% at Kathmandu and Pokhara and 6% Biratnagar in the year 2009 and 2010. It is also noted that Lukla is clearer among the four stations. This deviation might be due to effect of aerosols, humidity and non-ideal cosine response of the instrument. DOI: http://dx.doi.org/10.3126/jie.v8i3.5942 JIE 2011; 8(3): 169-175